THE CAUSALITY RELATIONSHIP OF DOW JONES INDUSTRIAL AVERAGE (DJIA) AND NIKKEI 225 TOWARDS JAKARTA COMPOSITE INDEX (JCI) PERIOD 2011 – 2016 - Ghiffari, Muhammad Fadhlan; Kindangen, Paulus; Tumewu, Ferdinand (FEB Universitas Sam Ratulangi Manado, 2018)
The openness of information between countries around the world is easier in this Globalization era, one country can share information through the internet as well as the economic condition of a country. A study about how is the influence of DJIA and NIKKEI 225 towards the JCI during 2011 to 2016 may help to identify the factors that make these indices related. The study aims to analyze the change of DJIA and NIKKEI 225 may influence the JCI during 2011 to 2016. The methodology used explanatory research which studying a situation to explain the relationship between variables. The sample used is the index historical data during 2011 to 2016 of the indices. The data analysis method using Granger’s Causality test with Vector Auto Regressive basis analyzed in EViews 9. The study found that there is no significant influence of DJIA towards the movements of JCI during 2011 to 2016, and NIKKEI 225 was significantly influenced the JCI in the period. There are several factors affecting these results such as trade ties between these countries, currency, foreign exchange reserve and the investment grade which affecting investors investment decision. For further research, the author recommend to add other global indices variables. Keywords: Stock Market, DJIA, NIKKEI 225, JCI, IHSG, Vector Auto Regressive, Granger’s Causality, Indonesia Stock Exchange.